Identifikasi Komponen Metabolit Sekunder yang Menentukan Toksisitas Ekstrak Daun Lansium domesticum Varietas Langsat - Fitriani; Ratna; Abraham; Rahman (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2022)
Research has been carried out on Secondary Metabolite Components Determining Toxicity of Lansium domesticum Leaf Extract of Langsat Variety with the aim of analyzing the toxicity of n-hexane, ethyl acetate and methanol fractions as well as identifying secondary metabolite components that determine the toxicity of Lansium domesticum leaf extract of Langsat variety. The method used was liquid-liquid extraction, then each fraction was tested for phytochemicals and tested for toxicity using the Brine Shrimp Lethality Test (BSLT) method. The results showed that the n-hexane fraction was dominated by steroids with a few polyphenols and tannins. The ethyl acetate fraction is dominated by polyphenols, tannins and alkaloids and still contains a small amount of steroids. The methanol fraction contains small amounts of polyphenols, tannins and saponins. Each fraction showed toxic activity against Artemia salina Leach larvae. The ethyl acetate fraction showed the highest toxic activity (LC50 of 75.24 ppm), followed by the methanol fraction (LC50 of 104.97 ppm) and lastly the n-hexane fraction (LC50 of 309.03 ppm). The components of secondary metabolites that greatly determine the toxic activity of the methanol extract of the leaves of L. domesticum of the langsat variety are polyphenols and tannins.